Study of Utilization of Antiplatelet Agents in Coronary Heart Disease Patients in Private Hospital in Surabaya - Ike Dhiah Rochmawati; Zakiah Rizka Rachmadania Arifin (Universitas Lambung Mangkurat, 2020)
ABSTRACT Antiplatelet is the most commonly drug used as secondary prevention for Coronary Heart Disease (CHD). The aim of this study was to determine the profile of the use of antiplatelet related with its efficacy and side effects. Observational methods with cross sectional approach for 3 months follow up was used, a descriptive analysis carried out at the private hospital in Surabaya. Results from this study: aspirin 80 mg was the most prescribed antiplatelet in patients with the incidence of ischemic events 9%. Higher ischemic events also seen in patients with hypertension, dyslipidemia, and Diabetes Mellitus. Bleeding and gastrointestinal disturbance as side effects occurred in 4 patients who used aspirin as antiplatelet, and based for Naranjo scale can be concluded as possible adverse drug reaction. Keywords: Coronary Heart Disease, Antiplatelet , Ischemic events, Bleeding